HIV General Population Surveys: Shedding Light on the Status of HIV Epidemics and Informing Future Actions. (1st August 2021) - Porter, Laura; Bello, George; Nkambule, Rejoice; Justman, Jessica
Abstract : Abstract: Nationally representative household surveys of the general population can provide critical assessments of the status of HIV epidemics and the impact of national HIV programs. With lessons learned from earlier surveys, PEPFAR has supported HIV-focused surveys in high burden countries to measure known HIV status, access to HIV treatment, and viral suppression, and, by using novel HIV recency assays, to estimate HIV incidence. The results from the initial population-based HIV impact assessments have transformed global HIV programming, demonstrating unexpected progress in population viral suppression and the persistent burden of high HIV incidence among adolescent girls and young women. The findings highlight the importance of tailoring programs to engage men more effectively in HIV testing and treatment. The collection of manuscripts summarized in this overview of the Supplement describe the methods and selected key findings from the initial population-based HIV impact assessment surveys. Taken together, the efforts described in these manuscripts have advanced survey and laboratory capacity and guided HIV programs toward the goal of ending the global epidemic.